NEON : addressing the nation's environmental challenges (Online access: National Academy of Sciences National Academies Press., 2004)
The book endorses the National Science Foundation's concept of the National Ecological Observatory Network (NEON) for providing a nationwide network of facilities and infrastructure for ecological and environmental research that is impossible with existing infrastructure. The committee identified six grand challenges in environmental biology - biodiversity, biogeochemical cycles, climate change, ecology and evolution of infectious diseases, invasive species and land and habitat use -- that deserves high priority for research and needs to be addressed on a regional or continental scale. However, the book says that NEON needs a refined focus and a more detailed plan for its implementation to ensure the maximization of its contribution to science and to better fit within the purview of Major Research Equipment and Facilities Construction funding.